MO494INSIDE CKD: MODELLING THE ECONOMIC BURDEN OF CHRONIC KIDNEY DISEASE IN EUROPE USING PATIENT-LEVEL MICROSIMULATION. (29th May 2021) - Abdul Sultan, Alyshah; Ärnlöv, Johan; Cabrera, Claudia; Card-Gowers, Joshua; De Nicola, Luca; Garcia Sanchez, Juan Jose; Halimi, Jean-Michel; Mennini, Francesco Saverio; Navarro-González, Juan F; Nolan, Stephen; Power, Albert John; Retat, Lise; et al.
Abstract: Background and Aims: Chronic kidney disease (CKD) is a debilitating and costly condition, affecting approximately 10% of people globally. Progression of CKD is associated with an increased incidence of adverse renal and cardiovascular outcomes, and premature mortality, as well as increased requirement for renal replacement therapies (RRTs), which are associated with significant healthcare costs and resource use. The trajectories of CKD prevalence, progression, outcomes and the related costs are therefore critical considerations for public health and policy planning. Using country-specific, patient-level microsimulation, Inside CKD aims to model the global clinical and economic burden of CKD from 2020 to 2025. Method: We used the Inside CKD microsimulation to model the economic burden of CKD in Europe. A virtual general population was developed for each country using national survey data and relevant data from published literature. Data inputs included country demographics, the prevalence of CKD and RRT, comorbidities and complication rates, as well as associated healthcare costs. CKD stages were defined according to Kidney Disease Improving Global Outcomes (KDIGO) 2012 recommendations and patients were categorized according to estimated glomerular filtration rate and albuminuria status. RRT modelling was calibrated against historical trends from country-specific renal registries. Model validation and calibration were conducted following established methods for health economic modelling. Here, we report the initial results from the UK analysis, with further analyses currently underway for additional European countries. Results: The UK analysis revealed that annual healthcare costs associated with CKD will increase linearly from £12.51B to £13.99B between 2020 and 2025. The largest absolute increase in cost was observed in CKD stage 3b (£0.75B); however, CKD stage 5 had the largest relative increase in cost with an approximately three-fold increase (£0.14B to £0.41B). By 2025, costs associated with CKD will increase across all age categories (18–34, 35–64 and 65+ years); the 35–64 age group had the largest absolute increase in costs with an increase of £1.14B (£2.02B to £3.16B). The largest relative increase in cost was observed in the 18–34 age category, with a three-fold increase in costs (£0.09B to £0.27B). Conclusion: Initial results from Inside CKD demonstrate that CKD poses a significant economic burden over the next 5 years. CKD stages 3b and 5 were associated with the most pronounced cost increases, likely due to increased prevalence for stage 3b and greater treatment cost for stage 5. Notably, the largest increase in CKD costs was observed in the 35–64-year-old 'working' population. Further policy interventions aimed at early diagnosis and proactive management should be considered to slow disease progression, improve patient outcomes and reduce the economic burden associated with CKD.